Greening industrialization in Sub-Saharan Africa - Luken, Ralph Andrew; Clarence-Smith, Edward (Routledge, 2020)
This book explores the concept of greening industrialisation and issues and considerations surrounding it through the lens of Sub-Saharan Africa. The book critically examines the concept of greening industrialisation and describes the progress and data challenges of monitoring the Sustainable Development Goals confronting African countries. The chapters summarise the policy and programme literature focused on eight policy regimes essential for greening industrialisation and identify opportunities for greening industrial policies. The authors lay out a research agenda that would inform, enable, and support greening industrialisation in Sub-Saharan Africa and provide an overview of green industrial plans that include climate strategies, energy efficiency strategies, and green industry assessments. This book will be of great interest to students, scholars, policy-makers, and planners in the fields of Sub-Saharan African development and African environmentalism